FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU PENCEGAHAN IMS PADA WANITA DI PROVINSI JAWA TENGAH - Elisa Nurhayati; Atik Mawarni; Farid Agushybana (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
Prevention of Sexually Transmitted Infections is one of the priorities of the World Health Organization 2016-2021. Women are a group that is still unfamiliar with STI prevention behavior, especially in terms of seeking information and treatment of STIs in health services. Some of the factors related to STI prevention behavior are age, latest education, marital status, residence, level of knowledge, and attitudes. This study aims to analyze the relationship between age, latest education, marital status, residence, level of knowledge, and attitudes with STI prevention behavior. The study was conducted using data from the 2017 IDHS (Indonesian Health and Demographic Survey). The sample consisted of 3,414 women in Central Java Province. Data analysis used chi-square test and logistic regression. Latest education (p-value = 0.009), marital status (p-value = 0.033) and level of knowledge (p-value = 0.008) are associated with STI prevention behavior, while age, residence, and attitude have no significant relationship with STI prevention behavior. The logistic regression test results showed that there was an influence between latest education (OR = 1.134), marital status (OR = 1.124), and level of knowledge (OR = 1.139). This study concludes that there is a significant relationship between latest education, marital status, and level of knowledge with STI prevention behavior.